PERANCANGAN MODEL PENGEMBANGAN KAPASITAS PELAKU WISATA DI BUKIT PARALAYANG KULON PROGO MELALUI STRATEGI PELATIHAN TERPADU - Astuti, Yenni; Kusumaningrum, Maria Asumpta Deny; Funny, Rindu Alriavindra; Rahmawati, Fajar Khanif (Fakultas Teknologi Informasi dan Industri Unisbank, 2025)
Giri Sembung Paragliding Hill, located in Banjarasri Village, Kulon Progo, is an emerging tourism destination managed independently by the local community. To support the capacity development of tourism actors, this community service program aims to design a modular and practical training model. The model consists of three complementary phases: (1) tourism communication training (English language), (2) digital promotion and content creation training, and (3) tourism management and service training. The implementation method adopts a participatory approach, grounded in field observations, discussions with local partners, and reflections from the initial phase of training. The developed model is flexible and can be implemented in stages according to the readiness of the community. Initial validation shows that the model is relevant, beneficial, and potentially replicable in other community-based tourism destinations with similar characteristics. This initiative is expected to contribute meaningfully to the professional development of community-based tourism actors and to enhance the competitiveness of local tourism destinations.